P2 Presence of fibular positional faults in individuals with chronic ankle instability. (17th September 2017) - Wellin, BW; Locke, C; Kingma, J; Staser, J; Docherty, CL
Abstract : Study Design: Case-Control Study. Objectives: To investigate the position of the distal fibula in individuals with unilateral chronic ankle instability (CAI) and healthy individuals. Background: CAI is classified as the presences of residual instability and episodes of 'giving way' which occurs following a lateral ankle sprain. It has been theorised that a fibular positional fault occurs following a lateral ankle sprain and this 'shift' may contribute to the ongoing ankle instability. Methods and Measures: Twenty-five subjects with unilateral CAI (height=170.49±9.42 cm, weight=73.66±16.21 kg; age=19.8±1.8 years) and twenty-five subjects with healthy ankles (height=168.36±14.78 cm, weight=73.34±26.35 kg; age=19.7±1.6 years) participated in this study. CAI was identified as anyone scoring an 11 or greater on the Identification of Functional Ankle Instability questionnaire on the affected ankle and zero on the contralateral limb. Healthy subjects had no history of ankle injury on either side. Subjects were fitted with a night splint and positioned side lying on an L board to ensure neutral ankle and hip positioning. A single lateral radiograph was taken of the ankle and this process was repeated on the contralateral limb. A licensed radiologist measured the distance (mm) between the most anterior portion of the tibia and the most anterior portion of the fibula. Results: Results of the RMANOVA yielded no significant side by group interaction (F11, 48 =1.75, p=0.19) and no significant differences between the sides or groups (p>0.05). Conclusions: It appears that these individuals with CAI did not have a significant shift in fibular position compared to the contralateral healthy limb or healthy individuals with no history of ankle sprains.